Malliavin Calculus and Stochastic Analysis A Festschrift in Honor of David Nualart - Viens, Frederi; Feng, Jin; Hu, Yaozhong; Nualart , Eulalia (Springer Proceedings in Mathematics & Statistics, 2013)
The stochastic calculus of variations of Paul Malliavin (1925 - 2010), known today as the Malliavin Calculus, has found many applications, within and beyond the core mathematical discipline. Stochastic analysis provides a fruitful interpretation of this calculus, particularly as described by David Nualart and the scores of mathematicians he influences and with whom he collaborates. Many of these, including leading stochastic analysts and junior researchers, presented their cutting-edge research at an international conference in honor of David Nualart's career, on March 19-21, 2011, at the University of Kansas, USA. These scholars and other top-level mathematicians have kindly contributed research articles for this refereed volume.